2020
DOI: 10.1111/cea.13668
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery and the risk of atopic dermatitis in children

Abstract: BackgroundCaesarean delivery (C‐section) may disrupt maternal‐infant microbial transfer and alter immune system development and subsequent risk for atopic dermatitis.ObjectiveInvestigate the association between C‐section and atopic dermatitis by age four and examine potential sources of bias in the relationship in a large cohort study.MethodsMaternal and child information was collected through Kaiser Permanente Northern California's (KPNC) integrated healthcare system. Data sources included electronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…As shown in Figure 1, a total of 1597 records were identified: 263 from PubMed, 568 from Embase, 95 from Cochrane, 296 from Web of Science, and 375 from Scopus. According to the inclusion and exclusion criteria, 13 studies 14‐18,21‐28 were included in the research and 12 studies 15‐18,21‐28 were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 1, a total of 1597 records were identified: 263 from PubMed, 568 from Embase, 95 from Cochrane, 296 from Web of Science, and 375 from Scopus. According to the inclusion and exclusion criteria, 13 studies 14‐18,21‐28 were included in the research and 12 studies 15‐18,21‐28 were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1 (the specific data are provided in the supporting information: Supplementary specific study characteristics). A total of 13 studies 14‐18,21‐28 with a total of 114 485 participants were included in this systematic review and meta‐analysis. Sample sizes ranged from 339 to 38 874 participants, and age at outcome ranged from 6 months to 17 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have not yet successfully explained the marked variations seen between and within countries in eczema prevalence. Hygiene hypothesis type exposures such as antibiotics or mode of birth do not always associate with eczema in the same way as for other atopic disorders 5 . Perhaps the leading area of investigation for eczema prevention at the moment is work on skin barrier integrity, informed by our understanding of the role of defects in epidermal barrier function in disease onset.…”
mentioning
confidence: 99%